Business scrum: A conceptual framework for agile business modelling - Khan, Ammar (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Business model innovation (BMI) is essential in today’s competitive business landscape because companies need to stay ahead of the curve by innovating and reinventing their business models, especially new companies. BMI process frameworks are a way to conduct business model design and innovation. However, based on the few existing BMI process frameworks, as far as we know, there are no frameworks that are both agile and systematic and that can reduce time-to-market for companies. This thesis aims to fill the research gap by presenting a conceptual framework, referred to as ‘business scrum’, which adopts key elements of agile scrum to the BMI process. The framework can be utilized by companies to design and innovate their business models in an agile, fast and systematic manner. This study is conducted using the design science research process which consist of five phases. In the first phase, a need for business scrum framework is identified from a prior research paper. In the second phase, a literature review of business model innovation process and agile scrum is conducted to find their key elements that can help to define the requirements for designing the business scrum framework. In the third phase, business scrum conceptual framework is developed by combining and adopting agile scrum’s phases, roles and its iterative nature to BMI process. In the fourth phase, the designed conceptual framework is evaluated and validated in a workshop with academic experts in business model domain, in which few improvements are identified. To incorporate these improvements, third phase is revisited to enhance the business scrum framework and to make it in a more complete form based on the evaluation results. In the final phase, the enhanced conceptual framework is presented and the results of the study are discussed. The key finding of this study is the BMI process framework that consists of systematic and iterative designing of business models and proposes essential roles for the management and implementation of its framework. Theoretically, this research contributes to BMI literature by providing a new process framework that is systematic and agile. Furthermore, this study contributes to the literature of agile methodologies by expanding its use to BMI literature. Practically, this research contributes to new companies that are looking for creating and innovating business models, and to those that want to decrease their time-to-market with new products or services.